A Survey of Design Issues in Spatial Input - Hinckley, Ken; Pausch, Randy; Goble, John C.; Kassell, Neal F. (UIST '94 Proceedings of the 7th annual ACM symposium on User interface software and technology, 1994)
We present a survey of design issues for developing effective free-space three-dimensional (3D) user interfaces. Our survey is based upon previous work in 3D interaction, our experience in developing free-space interfaces, and our informal observations of test users. We illustrate our design issues using examples drawn from instances of 3D interfaces. For example, our first issue suggests that users have difficulty understanding three-dimensional space. We offer a set of strategies which may help users to better perceive a 3D virtual environment, including the use of spatial references, relative gesture, two-handed interaction, multisensory feedback, physical constraints, and head tracking. We describe interfaces which employ these strategies. Our major contribution is the synthesis of many scattered results, observations, and examples into a common framework. This framework should serve as a guide to researchers or systems builders who may not be familiar with design issues in spatial input. Where appropriate, we also try to identify areas in free-space 3D interaction which we see as likely candidates for additional research.